Construct Validity of the Participation and Sensory Environment Questionnaire–Teacher Version. (June 2019) - Piller, Aimee; Fletcher, Tina; Pfeiffer, Beth; Dunlap, Karen; Pickens, Noralyn
The Participation and Sensory Environment Questionnaire–Teacher Version (PSEQ-TV) is a teacher report questionnaire designed to examine the impact of the sensory environment on participation for preschool children with autism spectrum disorder (ASD). This study examines the construct validity of the assessment through principal components analysis (PCA). One hundred three preschool teachers completed the research version of the PSEQ-TV. Component analysis revealed six factors: modification, support, preschool tasks, group routines, mealtime, and tactile. This study provides evidence as to the construct validity of the PSEQ-TV. The PSEQ-TV can be used to identify sensory-related environmental barriers within the preschool environment. By identifying these barriers, teachers and other support staff can modify the environment and/or provide support to increase participation of preschool children with ASD across school environments.